2022
DOI: 10.1002/anie.202116534
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Removing Impurities in Nickel Oxide on High‐Efficiency and Long‐Term Stability of Inverted Perovskite Solar Cells

Abstract: The performance enhancement of inverted perovskite solar cells applying nickel oxide (NiOx) as the hole transport layer (HTL) has been limited by impurity ions (such as nitrate ions). Herein, we have proposed a strategy to obtain high‐quality NiOx nanoparticles via an ionic liquid‐assisted synthesis method (NiOx‐IL). Experimental and theoretical results illustrate that the cation of the ionic liquid can inhibit the adsorption of impurity ions on nickel hydroxide through a strong hydrogen bond and low adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 63 publications
1
78
0
Order By: Relevance
“…The reverse (forward) scan and detailed parameters are recorded in Figure a and Table 1 , which is consistent with our previous report. [ 35 ] The Control device displays a relative low V OC of 1.11 (1.10) V, J SC of 22.53 (21.89) mA cm −2 and FF of 80.40% (79.47%), thence an unsatisfactory PCE of 20.12% (19.20%). On the contrary, an improved PCE of 22.81% (22.13%) is observed in NiO x :TTTS device with enhanced V OC 1.15 (1.14) V, J SC 23.49 (23.15) mA cm −2 and FF 84.68% (83.84%).…”
Section: Resultsmentioning
confidence: 99%
“…The reverse (forward) scan and detailed parameters are recorded in Figure a and Table 1 , which is consistent with our previous report. [ 35 ] The Control device displays a relative low V OC of 1.11 (1.10) V, J SC of 22.53 (21.89) mA cm −2 and FF of 80.40% (79.47%), thence an unsatisfactory PCE of 20.12% (19.20%). On the contrary, an improved PCE of 22.81% (22.13%) is observed in NiO x :TTTS device with enhanced V OC 1.15 (1.14) V, J SC 23.49 (23.15) mA cm −2 and FF 84.68% (83.84%).…”
Section: Resultsmentioning
confidence: 99%
“…The record PCE is over 22% of the MAPbI 3 -based inverted PSCs with NiO x HTL. [10][11][12] To date, the NiO x HTL in inverted PSC has been prepared by various methods, such as magnetron sputtering, electron beam deposition, pulsed laser deposition, and solution process. [13] Among them, the solution process to fabricate NiO x HTL has been considered a promising approach due to its simple fabrication, low cost, and high yield.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] On the other hand, recent studies revealed that the deprotonation and redox reactions between the organic iodide components in a perovskite absorber and Ni 3+ in the NiO x layer led to a relatively low device efficiency and stability. 12,15 Typically, Ni 3+ is a p-type dopant for improving the hole mobility of the NiO x films and could be easily generated by doping monovalent cations (such as Li + , Ag + , and Cs + ) or thermal annealing during the deposition processes, including spray-coating, atomic layer deposition, and sputtering. [16][17][18][19] To further improve the PSC performance, excess organic iodide salts were added into the perovskite layer to compensate for the loss of components near the NiO x contact, which enables the device efficiency approaching 20% and over a 500-hour operational lifetime.…”
Section: Introductionmentioning
confidence: 99%